On the optimal calibration of VVV photometry - Hajdu, Gergely; Dékány, István; Grebel, Eva K. (Experimental astronomy, 2020)
Prompted by some inconsistencies in the photometry of the VISTA Variables in the Vía Láctea (VVV) survey, we conduct a revision of the standard calibration procedure of VISTA data in the J, H, and KS passbands. Two independent sources of bias in the photometric zero-points are identified: First, high sky backgrounds severely affect the H-band measurements, but this can mostly be minimized by strict data vetting. Secondly, during the zero-point calibration, stars serving as standards are taken from the 2MASS catalog, which can suffer from high degrees of blending in regions of high stellar density, affecting both the absolute photometric calibration, as well as the scatter of repeated observations. The former affects studies that rely on an absolute magnitude scale, while the latter can also affect the shapes and amount of scatter in the VVV light curves, thus potentially hampering their proper classification. We show that these errors can be effectively eliminated by relatively simple modifications of the standard calibration procedure, and demonstrate the effect of the recalibration on the VVV survey’s data quality. We give recommendations for future improvements of the pipeline calibration of VISTA photometry, while also providing preliminary corrections to the VVV JHKS observations as a temporary measure.